To Find the Best Site for Urban Development in Prachuap Khiri khan, Thailand - Taniwall, Nasim Jan; Hassan, Samiullah; Haider, Muhammad Sharif; Sulaimanzai, Habibullah; Salih, Salih Khan (Integrated Journal for Research in Arts and Humanities, 2023)
Coastal areas in the western provinces of Thailand, a popular destination in Northern Thailand, are facing rapid tourism-related sustainable development issues and. This study aims to find the coastal areas which need to be conserved for tourism and find the areas which are safer and suitable for urban development in Prachuap Khirikhan province. Multiple criteria evaluation (MCE) and several available tools in GIS such as ‘Reclassify’, ‘Overlay’, ‘Proximity’, ‘Spatial analyst tools’ etc. are used during analysis. ‌Based on the available data and multi-criteria analysis, the area in the Prachuap Khirikhan has been classified into five categories from “Highly Suitable” to “Not Suitable. The results show that there are large number of Tambon which are highly suitable for urban development such as Phung Prasan, Kamnoet Nopphakhun, Thong chai, Thap sake, Huai Yang, Huai sai, Khlong Wan, Ko Lak, Ao Noi, Bo Nok. The Tambons which are found “Not suitable” or “Low suitable” for urban development are Nong Phap, Nong Ta Taem, Sila Loi and Chang Raek.